Free convection in inclined hemispherical cavities with dome faced downwards. Nu-Ra relationships for disk submitted to constant heat flux - Bairi, A.; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2014)
The objective of this survey is to quantify the free convective heat transfer that occurs in hemispherical air-filled cavities. The disk constitutes an active electrical assembly designed to control systems used in various engineering applications as in solar energy and domotics. In safety and security fields, hemispherical cavities are widely used to control recording, warning and emergency systems. The dome of the considered enclosures is maintained isothermal while the disk constituting the control system is subjected to a constant heat flux. It is inclined at an angle varying between 90 degrees (vertical position) and 180 degrees (disk horizontal with dome oriented downwards). The numerical approach is performed by means of the finite volume method for Rayleigh numbers in the range 10(4)-5 x 10(8). Calculations are confirmed by measurements, leading to new Nusselt-Rayleigh type correlations which allow correct thermoregulation of the disk and ensure optimal operation of the considered assembly. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Heat transfer; Natural convection; Tilted hemispherical cavities; Experimental approach; CFD; Engineering applications; Neumann-type boundary condition